Bidirectional Loading History for Seismic Testing of 3D Frame Joints - Vinay Mahadik; Akanshu Sharma (CivilEng, 2021)
Beam-column-joints (BCJ) in reinforced concrete (RC) frames are known to be critical against seismic actions. Hence, several researchers have conducted related investigations. The loading history used in the experimental investigations must be a sufficiently accurate and conservative representation of seismic loading on the structure and should trigger all possible critical failure mechanisms in the subassembly. Presently, there is significant diversity in the loading histories used for seismic investigation of structural subassemblies. This paper intends to propose an optimum loading history for considering bidirectional (horizontal) seismic action on 3D-RC BCJ subassemblies. To this end, the available loading histories (unidirectional and bidirectional) for simulation of seismic loads on RC joint subassemblies are reviewed in the context of the demands they impose on the joints. Finite element modeling and analyses are used as a tool for investigating the response of 3D-BCJ subassembly under different bidirectional loading states.